Gastrointestinal Langerhans cell histiocytosis responding to cladribine and imatinib mesylate - Agreda Vásquez, Gladys Patricia; Popoca Barriga, Ulises; Oviedo, Edgar; Lome Maldonado, Carmen; Sánchez Guerrero, Sergio Arturo (UANL Facultad de Medicina, 2010)
Gastrointestinal involvement in Langerhans cells histiocytosis (LCH) is extremely rare. An optimal treatment regimen is not defined yet and its prognosis is relatively poor. Cladribine, and more recently, Imatinib mesylate (IM) have been recommended as treatment options in refractory LCH. Here we present a case of gastrointestinal involvement in an adult patient with LCH refractory to several treatment regimens who responded nicely to cladribine and currently treated with IM 300 mg/day, as maintenance, for the last 24 months.